Simulation-Based Analysis of Additive Manufacturing Systems for Fuel Nozzles - Trancoso,João Pedro Grobberio (2018)
ABSTRACT: Additive manufacturing technologies have the potential to revolutionize manufacturing, allowing for the production of ever more complex products and supporting the creation of strategic competitive advantages to certain industries. Recent investments in additive manufacturing systems show that operational plants are close to become reality. In this context, the demand for knowledge regarding the behavior of such systems is expected to increase. This research aims to analyze additive manufacturing systems - based on powder bed fusion technologies - applied to aerospace fuel nozzles by modeling and simulating different scenarios regarding the allocation of resources. The amount of time required by the additive step is a key aspect of the plants behavior and, still, there is a limit to the increase in productivity attained by adding more parts per batch. Different combinations of productive resources showed that the optimization of resources utilization is bounded by the number of additive manufacturing machines. Furthermore, total unit costs are mostly driven by the equipment costs as the need for human resources is significantly reduced.